Autistic Acceptance, the College Campus, and Technology: Growth of Neurodiversity in Society and Academia - Robertson, Scott M.; Ne'eman, Ari D. (Disability Studies Quarterly, 2008)
This paper presents an in-depth examination of autistic acceptance on college campuses from the perspective of two academic scholars who are both autistic.1 This inquiry first describes the history of the emergence and growth of the neurological diversity and autistic rights movements. These movements led to the development of a unified autistic disability culture and community. Then the paper shares how autistic acceptance on college campuses has received increasing attention in parallel with expanded focus on autistic acceptance in society. It highlights major challenges impacting autistic people attending colleges and universities, as well as potential solutions for resolving those challenges and cultivating understanding and support of autistic people among the broader culture of colleges and universities. This paper examines the emergence of autistic acceptance in society and the growth of support for autistic people on the college campus. It is written from the authors' perspectives as autistic persons who pursued college studies, and both authors are active scholars and advocates in the cross-disability community.